2018
DOI: 10.1590/s1519-99402018000100005
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient and amino acids composition of milk replacers for dairy calves

Abstract: SUMMARY Other than crude protein (CP), crude energy (CE) and crude fiber (CF) content, the adequate supply of essential amino acids (EAA) is an important factor in milk replacer evaluation. The aim of this study was to analyze milk replacer samples as regard to nutrients, especially EAA, composition and simulate the attainability of calves' requirements in different feeding systems. Forty-one milk replacer samples were collected from 14 brands and analyzed for nutrient composition. The near infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
0
12
1
7
Order By: Relevance
“…Recent research has shown the benefits of increasing weight gain of dairy calves, mainly by feeding higher levels of liquid diet [ 1 , 2 ], even if there is an impact on the raising daily costs. Feeding with milk replacer (MR) can be an alternative to reduce costs, but it can result in different performance when feeding the same volumes due to differences in crude protein (CP) and fat content when compared to whole milk [ 3 ]. Furthermore, the inclusion of non-dairy protein sources can cause amino acid imbalance and difficulty in meeting the calves’ needs to achieve a desirable growth rate [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown the benefits of increasing weight gain of dairy calves, mainly by feeding higher levels of liquid diet [ 1 , 2 ], even if there is an impact on the raising daily costs. Feeding with milk replacer (MR) can be an alternative to reduce costs, but it can result in different performance when feeding the same volumes due to differences in crude protein (CP) and fat content when compared to whole milk [ 3 ]. Furthermore, the inclusion of non-dairy protein sources can cause amino acid imbalance and difficulty in meeting the calves’ needs to achieve a desirable growth rate [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even when calves are fed whole milk, considered the best source of protein due to its high digestibility and AA profile, the Met concentration is below ideal levels for improved calf performance [ 4 , 12 , 15 ]. Besides, calves fed a medium CP milk replacer do not meet the requirements recommended by Hill et al [ 12 ] when moderate volumes such as 6 L/d are fed [ 3 ]. Other studies suggested that the industry should consider synthetic AA supplementation in MR formulation to improve the performance of dairy calves [ 3 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Talvez haja a possibilidade desse gênero se expressar também em momentos de disbiose, para ajudar a manter a homeostase intestinal. Como os sucedâneos lácteos disponíveis no mercado apresentam variação em sua composição (Bittar et al, 2018), alguns autores comentam que seja possível a presença de alguns oligossacarídeos, que podem ser importantes no estabelecimento de uma microbiota intestinal benéfica, que podem atuar como componentes alimentares bioativos de alto potencial (Barile et al, 2009;Aldredge et al, 2013;. Esses dados talvez ajudem a entender o porquê do sucedâneo estimular a maior abundância desse gênero.…”
Section: Discussionunclassified
“…Em algumas situações, o fornecimento de leite integral é substituído por fórmulas comerciais (sucedâneos lácteos), seja por motivos econômicos, de constância na composição da dieta líquida ou pela oportunidade de aumentar o teor de sólidos da dieta líquida. Muitos estudos mostram que os sucedâneos podem ser adequados para substituir o leite, garantindo o desempenho animal, desde que tenham composição adequada em fontes e níveis de nutrientes (Cooper e Watson, 2013;Bittar et al, 2018;Bai et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation